The use of Malaysian English lexical terms in the work of Preeta Samarasan / Prema Jaya Balan - Jaya Balan, Prema (2012)
This research is a study on how Malaysian English is used in creative writing by a Malaysian writer. It studies the novel ‘Evening is a whole day’ by Preeta Samarasan. Focusing on the extraction and categorisation of Malaysian English lexical items and semantic terms used by a Malaysian writer, this research sets out to study the extent to which the writer uses lexical items and semantic terms from the non-native variety in her prose writing. Language purists have often accused non-native varieties as being the result of a failure of approximation. The deviations in these varieties are seen in a negative light and therefore the non-native varieties are considered inferior to Standard British English. If that is the case, the question arises as to why writers who are educated speakers of the language choose to use the local variety in their works. Analysis of data using Baskaran’s (2005) categorisation shows that the writer uses non-native lexical items in her writing. She also uses non-native semantic transfers based on the framework from Menon (2003). These findings show that although there are equivalents in the English language, the writer consciously chooses to use local words in her writing. This is clearly seen in the dialogues. The writer seems to have done this to depict the actual linguistic scenario in the country as the story studied here has a Malaysian setting. Thus, the study shows that there is a need for the use of Malaysian English in creative writing when the situation requires its usage. The use of local lexis items and semantic terms in the creative writing which gives our home grown variety of English a distinct and unique flavor should make it more acceptable and recognised as a legitimate sibling of Standard British English and not as an enigma to be hidden in the closet. It shows that the Malaysian variety is known around the globe as a branch in the Varieties of English tree.